186 System wide integration of mental health into diabetes transformation: A model for other long term conditions?. (16th November 2020) - Sachar, Amrit; Willis, Tony
Abstract : North West London (NWL) has 8 CCGs, in a diverse area with significant deprivation and a complex commissioning landscape. Self-care is central to diabetes management but self-care is negatively affected by mental illness which is common in diabetes. Improving MH improves diabetes outcomes. In NWL, about 79, 000 people with diabetes (PWD) may be struggling with MH issues but there is variation in MH service provision, no standard MH screening, so data analysis is challenging, and only 15wte staff working in diabetes MH across 8 CCGs. Intervention: We used small, short term funding to build sustainable change rather than deliver a finite clinical service to a small number of PWD. We mobilised a Model for Improvement approach with a simple driver diagram to implement system-wide interventions. MH was fully embedded throughout the entire suite of products we had in NWL including 10-year service specification, clinical guidelines, training for staff and PWD, digital platform. Impact: Behaviour and culture change for clinicians, commissioners, public; diabetes/anxiety screening rates in PWD went from 4% to 38% (59, 000) of PWD; improved MH detection led to improved collaborative care planning (80%), take up of patient education programmes (30%), and reduction of diabetes complication admissions (12%) in 12 months. Conclusion: A system-wide approach using a simple driver diagram is useful for taking a wide view of the issues and for engaging stakeholders. The first author has used a similar driver diagram for NWL renal care and is now working with Kidney Care UK to create a MH pathway for kidney care using this driver diagram as a starting point. The model is potentially transferrable to other long term conditions. Lessons for Leaders: Articulate a clear, co-created message. Galvanise a strong coalition of engaged stakeholders and those voices will disseminate the message. Use small, short term resource to create system change wherever possible to get sustainable.